2023
DOI: 10.3390/nu15071552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protein Supplementation Combined with Resistance Exercise Training on Walking Speed Recovery in Older Adults with Knee Osteoarthritis and Sarcopenia

Abstract: Knee osteoarthritis (KOA) is closely associated with sarcopenia, sharing the common characteristics of muscle weakness and low physical performance. Resistance exercise training (RET), protein supplementation (PS), and PS+RET have promise as treatments for both sarcopenia and KOA. However, whether PS+RET exerts any effect on time to recovery to normal walking speed (WS) in older adults with sarcopenia and KOA remains unclear. This study investigated the treatment efficiency of PS+RET on WS recovery among indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Additional dietary supplements could restore the patients to normal walking speed 3 months earlier. 131 Zhao et al found that a whey protein supplement of 10 g/day combined with RT can effectively improve the SMM of the limbs of inflammatory bowel disease patients. 132 Kemmler et al conducted high-intensity dynamic RT combined with whey protein supplement intervention on 43 male patients with osteoporosis who were older than 72, and the lumbar bone density and SMI of the intervention group were significantly improved after 18 months.…”
Section: Combining Exercise With Dietary Supplementsmentioning
confidence: 99%
“…Additional dietary supplements could restore the patients to normal walking speed 3 months earlier. 131 Zhao et al found that a whey protein supplement of 10 g/day combined with RT can effectively improve the SMM of the limbs of inflammatory bowel disease patients. 132 Kemmler et al conducted high-intensity dynamic RT combined with whey protein supplement intervention on 43 male patients with osteoporosis who were older than 72, and the lumbar bone density and SMI of the intervention group were significantly improved after 18 months.…”
Section: Combining Exercise With Dietary Supplementsmentioning
confidence: 99%